Commercial-scale adoption of improved cassava varieties: A baseline study to highlight constraints of large-scale cassava based agro-processing industries in Southern Nigeria - Tarawali, G.; Iyangbe, C.; Udensi, U.E.; Ilona, Paul; Osun, T.; Okater, C.; Asumugha, G.N. (2012)
Cassava is an important food security crop among smallholder farmers in Southern Nigeria, because it can tolerate drought, low soil fertility and its production requires minimum external inputs. In most African countries, cassava is becoming important cash crop that has high potential for use as an industrial raw material to manufacture starch and flour. The use of cassava flour in confectionery industries recently in Nigeria is new and fast gaining ground. One major constraint faced by the cassava industrial sector is inadequate supply of raw material to boast the industry. This has been attributed to poor yield and harvest from farmers’ field, due to several and interrelated factors. Most significant of these factors is lack of large-scale adoption and cultivation of improved cassava varieties. Various constraints have militated against the widespread adoption of improved cassava varieties, with effect evidenced in the poor supply of raw material need of cassava based agro-processors. This study examined these factors in eight States of Southern Nigeria, using the probit model. Sixty-eight cassava farmers from the eight project states were randomly selected using a multistage random sampling procedure during 2008/2009 planting season. Results of the study showed that 23.5% of the respondents were females, while majorities (76.5%) were male. Only about 46% of the farmers were in their productive years (21-50 years), while the majority (54.0%) consisted of those who were >50 years. The average of the farmers was about 50 years, with more than 50% having greater than 15 years farming experience. About 59% of the respondents were basically small-holder farmers with farm size less than one hectare; while 41% had farm size between 1 and ≥ 5 ha. Of the 68 respondents, majority (60%) farm on family land, while 40% of them were leaseholders. Land use practices varied among the farmers. Results indicated that 73% of 68 farmers who responded adopted fair land use practices while 16% observed good land use practices. However, about 11% of the respondents maintained a poor land use practice. The results of this study also showed that 66% of the farmers adopted improved cassava variety, either solely or in combination with local varieties; while about 34% of the farmers still rely on their local variety. However, less than 30% of the farmers using improved variety adopted improved crop management practices. Yield from the farmers’ field averaged 13.6 ton ha-1. The study also observed that 68% of the cassava roots sold for family income, were sold at the farm-gate, village and urban markets, and seldom to the agroprocessors; while 32% were reserved for household consumption. The coefficient for gender, cassava yield and farming experience were positivelyrelated to adoption of improved varieties. However, gender and yield had a significant relationship at 5% level of probability, while years of farming experience was not significant at 5% but at 10% level. Land ownership on the other hand had negative effect, significant at 5% level of probability. Implicit in these results is that farming experience and level of yield obtained may determine a farmer’s willingness to commercially adopt improved variety. Similarly, the profitability arising from increased yield from improved variety may prompt more farmers to adopt and hence expand their holding and land use, with more leaseholder of land increasing.